Pelatihan Penggunaan Tensimeter Manual Bagi Kader Posyandu Di Wilayah Desa Bawak Cawas, Klaten - Endang Sawitri; Wiwin Rohmawati; Anna Uswatun Qoyyimah; Agustina Agustina (Universitas Muhammadiyah Klaten, 2024)
Non-communicable diseases (NCDs) are diseases that cannot be transmitted from person to person, whose development occurs slowly over a long period of time (chronic). In the initial course, NCDs often have no symptoms, many do not know and are aware that they have the disease. Efforts to control non-communicable diseases (PTM) such as: hypertension, etc., can be carried out by means of routine control at community health centers or through services at posyandu. Activities at the posyandu are coordinated by posyandu cadres. One of the activities carried out at the posyandu is health screening by measuring blood pressure. There are many posyandu cadres who have not mastered the skills of using manual blood pressure monitors. There needs to be training in using manual blood pressure monitors at posyandu. The goals of this activity is to increase knowledge and skills on how to use a blood pressure measuring device in the form of a manual blood pressure monitor for posyandu cadres in the Bawak Village Area, Cawas, Klaten. The methods used are socialization, preparation, implementation and evaluation. Training was carried out on a cadre of 17 people. All posyandu cadres were able to demonstrate well and were skilled at using a manual sphygmomanometer to measure blood pressure.